Percepção dos professores sobre metodologias ativas : reflexões sobre a profissão docente - Penna, Bruno Paixão (2024)
This document is a report on research that aimed to investigate the perceptions of Natural Sciences teachers in the state education network of the municipality of Cachoeiro de Itapemirim/ES regarding Active Methodologies (AM). This was done through an analysis of the teachers’ narratives about lesson development using AM. The idea for the research arose in the context of the growing encouragement by the State Government’s Department of Education (Sedu) to incorporate AM into teachers’ lesson plans. This incentive is accompanied by various continuing education courses designed to prepare teachers to incorporate the “pedagogical innovations” of AM and digital technologies. How these training processes unfold and their respective effects on teachers’ performance may indicate the direction the teaching profession is heading. In this context, the following research question was developed, guiding all stages of the study: What do the perceptions of Natural Sciences teachers in the state education network in Cachoeiro de Itapemirim/ES regarding AM suggest about their training processes and professional spaces? This is a qualitative study of the Narrative type. The tools used for data collection were Narrative Interviews and Field Diaries. Four teachers were selected to participate in the interviews. The narratives were audio recorded and later transcribed, forming the corpus for analysis in the study. The technique used for data analysis was Thematic Analysis, from which three themes emerged from the narratives. The interpretation of these themes, based on the theoretical framework of the study, allowed for addressing the research question. The results indicate that teachers perceive lesson planning using AM as a challenge, given the unfavorable working conditions they face. It was also noted that the training processes related to AM exhibit a technical rationality, with little room for reflection or for valuing teachers’ experiential knowledge. Additionally, it was found that the current scenario of state public education aligns with market interests, with increased participation of private sector actors in the provision of educational services. Thus, the conclusion of the analysis suggests that the promotion of AM teaching by Sedu is more aligned with market interests and the expansion of neoliberal policies and practices, potentially accelerating the deprofessionalization of teaching